Inhibition of c-JNK/p38MAPK signaling pathway by Apigenin prevents neurobehavioral and neurochemical defects in ethidium bromide-induced experimental model of multiple sclerosis in rats: Evidence from CSF, blood plasma and brain samples - Anshuman Singh; Shubham Upadhayay; Sidharth Mehan (Elsevier, 2021)
Background: Multiple sclerosis (MS) is an idiopathic and autoimmune-mediated neurodegenerative disease that causes demyelination, neuroinflammation, and axonal loss in the central nervous system (CNS). MS is characterized primarily by motor and cognitive impairment. The current study reveals that the overactivation of c-Jun N-terminal kinases (JNKs) and mitogen-activated protein kinases (MAPK) signaling pathways are involved in the pathophysiology of MS. Apigenin (APG) is a naturally active phytoconstituent that shown neuroprotection via downregulating the c-JNK/p38MAPK signaling pathway. Purpose: The current investigation looked at the neuroprotective potential of APG (40-80 mg/kg) on behavioural, molecular, neurochemical, and gross pathological changes in intracerebropeduncle (ICP) ethidium bromide (EB) induced MS-like rats. Methods: In the present study, 36 rats were used; each group consisted of six Wistar rats (n = 6) treated with 0.1%/10 μl ICP-EB injection for seven days. From the eighth to the 35th day of the experimental protocol schedule, rats were evaluated for neuromuscular abnormalities using an actophotometer, motor deficits using a rotarod test, gait abnormalities using a beam crossing task (BCT), spatial learning, and memory consolidation using a Morris water maze (MWM). In CSF, blood plasma, and brain homogenate samples of EB-induced MS treated rats, neurochemical parameters were also assessed. Results: According to this research's findings, APG modulates the levels of c-JNK/p38MAPK and myelin basic protein in CSF and brain homogenate. Furthermore, APG restored aberrant levels of apoptotic markers (caspase-3, Bax, Bcl-2) in blood plasma and rat brain homogenate and lowered inflammatory cytokines (TNF-α, IL-1β). APG also reduced oxidative stress by increasing antioxidant enzymes and restored neurotransmitter levels. Our finding shows that APG has a neuroprotective effect in rats by improving gross pathological alterations and decreasing demyelination volume. In addition, APG appears to have neuroprotective effects against EB-induced motor dysfunctions in MS rats.